Investigating sarcopenia, physical activity, and inflammation biomarkers in newly diagnosed oral cancer patients undergoing curative treatment: A prospective longitudinal study - Chun-Hou Huang; Tai-Chu Peng; Yu-Fu Chou; Yun-Hsin Peng (Elsevier, 2023)
Objective: This prospective longitudinal study aimed to investigate changes in sarcopenia, physical activity, and inflammation biomarkers in patients with oral cavity cancer during curative treatment and explore their association with treatment outcomes. Methods: Patients newly diagnosed with oral cavity cancer who underwent primary surgery with (chemo)radiation therapy were included. Along with physical activity and inflammatory markers, sarcopenia was assessed using a 5-time chair stand test, hand grip strength, and skeletal muscle index (SMI). Data were collected before operation and after 3 months (T2) and 6 months after operation. Logistic regression and Cox proportional hazards models were used to identify predictors of treatment outcomes. Results: Out of 56 patients, 21 (37.5%) had sarcopenia. SMI score, physical activity, and neutrophil-to-lymphocyte ratio (NLR) showed significant changes after surgery, with exacerbation at T2. Patients with sarcopenia exhibited a significant decrease in SMI scores at T2. Advanced cancer stage and sarcopenia were associated with treatment-related dysphagia (odds ratio [OR] ​= ​3.01, P ​= ​0.034; OR ​= ​7.62, P ​= ​0.018). Sarcopenia (OR ​= ​3.02, P ​= ​0.002) and NLR (OR ​= ​5.38, P ​< ​0.001) were significantly associated with infections. Pretreatment SMI independently predicted poor survival outcomes (hazard ratio ​= ​7.00, P ​= ​0.005). Conclusions: Identifying patients with oral cavity cancer, sarcopenia, and high NLR levels can ensure prompt education and vigilant monitoring, potentially improving treatment outcomes and patient well-being during curative treatment.